Key factors influencing graduation on time among postgraduate students: a PLS-SEM approach / Priyadarshini Muthukrishnan ... [et al.] - Muthukrishnan, Priyadarshini; Sidhu, Gurnam Kaur; Teoh, Sian Hoon; Narayanan, Geethanjali; Chan, Yuen Fook (Universiti Teknologi MARA, 2022)
The information age witnessed the democratisation of education with an exponential growth in the enrolment of postgraduate students in almost all universities around the world. However, high attrition and low completion rates among students have been an immense threat to the key performance of the university system. The main purpose of this study was to investigate the influence of institutional support, supervisory practices, and students’ self-management and research skills on postgraduate students’ motivation to graduate on time (GOT). The data were collected from 191 postgraduate students from three universities in Malaysia using a survey questionnaire. The quantitative data were analysed using the PLS-SEM approach. The results revealed that research skills, institutional support and self-management skills significantly influenced the postgraduate students’ motivation to GOT. Furthermore, research skills were identified as the strongest predictor of the motivation to GOT. Additionally, research skills mediated the relationships between institutional support, students’ selfmanagement skills and postgraduate students’ motivation to GOT. However, supervisory practices toward GOT were not supported either by direct or indirect effect. The study has far reaching implications for the postgraduate students, supervisors, and institutions of higher learning.